(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To assess the efficacy of prolonged gas tamponade in patients with persistent idiopathic macular holes (IMHs) who had received a vitrectomy with classical internal limiting membrane (ILM) peeling. Material and Methods: Nine eyes (8 patients, including 7 women and 1 man; mean age [SD], 67.9 (7.5) years) with persistent IMHs were followed. In two eyes, a revision procedure without extended ILM peeling and with С3F8 15% tamponade was performed. In seven eyes, not a revision procedure, but a replacement tamponade with С3F8 15% was performed for prolonging the duration of С3F8 15% tamponade. Results: At 1-1.5 months after primary MH surgery, IMHs failed to close in all study eyes. Mean minimum MH size (SD) significantly improved in all eyes from 404.4 (131.4) µm to 282.1 (160.0) µm (р = 0.017). Mean best-corrected visual acuity (BCVA) (SD) improved from 0.11 (0.056) to 0.24 (0.13), р = 0.008. In all study eyes, with the prolonged duration of gas tamponade and two weeks of facedown positioning, IMHs closed and mean BCVA (SD) improved significantly (р = 0.003) to 0.43 (0.22). Conclusion: Prolonged С3F8 15% tamponade is an effective method of treatment for persistent IMHs after vitrectomy with classical ILM peeling.